2014
DOI: 10.1111/bju.12867
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic chemotherapy in the contemporary management of metastatic castration‐resistant prostate cancer (mCRPC)

Abstract: . contributed equally.For several years, docetaxel was the only treatment shown to improve survival of patients with metastatic castrationresistant prostate cancer (mCRPC). There are now several novel agents available, although chemotherapy with docetaxel and cabazitaxel continues to play an important role. However, the increasing number of available agents will inevitably affect the timing of chemotherapy and therefore it may be important to offer this approach before declining performance status renders pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…Chi et al (19) proposed that 12 months was the key time at which to evaluate responses to AR-targeting agents and recommended that patients showing shorter times to CRPC should be considered for upfront use of docetaxel. Sonpavde et al (20) proposed that a time of 16 months to CRPC should trigger upfront use of chemotherapy (20). In our present study, a time of 16 months to mCRPC significantly predicted a 50% PSA response.…”
Section: Discussionsupporting
confidence: 59%
“…Chi et al (19) proposed that 12 months was the key time at which to evaluate responses to AR-targeting agents and recommended that patients showing shorter times to CRPC should be considered for upfront use of docetaxel. Sonpavde et al (20) proposed that a time of 16 months to CRPC should trigger upfront use of chemotherapy (20). In our present study, a time of 16 months to mCRPC significantly predicted a 50% PSA response.…”
Section: Discussionsupporting
confidence: 59%
“… 22 Cytotoxin chemotherapy is a common type of chemotherapy and is widely used in systemic therapy for cancer treatment. 23 Previous studies have reported that radiotherapy or chemotherapy can lead to the measurable regrowth of tumor cells. 7 , 8 In addition, PGE 2 promotes the proliferation of cancer cells and stem cells in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is retrospective evidence to suggest that cabazitaxel before abiraterone acetate may be the preferred order after progression on docetaxel, but a prospective study would be necessary to clarify. 15 In addition, the increasing use of abiraterone acetate in prechemotherapy patients and recent approval of enzalutamide in this setting will likely narrow down the list of potential treatments after docetaxel. Molecular targeted therapies, next-generation antiandrogens, and immunotherapies are currently in the research pipeline and may further expand the list of treatment options both in the chemotherapy-naïve patient and postdocetaxel.…”
Section: Symptomatic Diseasementioning
confidence: 99%